2012
DOI: 10.1042/cs20120226
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic preconditioning enhances the therapeutic potential of the secretome from cultured human mesenchymal stem cells in experimental traumatic brain injury

Abstract: Bone-marrow-derived human MSCs (mesenchymal stem cells) support repair when administered to animals with TBI (traumatic brain injury) in large part through secreted trophic factors. We directly tested the ability of the culture medium (or secretome) collected from human MSCs under normoxic or hypoxic conditions to protect neurons in a rat model of TBI. Concentrated conditioned medium from cultured human MSCs or control medium was infused through the tail vein of rats subjected to TBI. We have demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
212
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(225 citation statements)
references
References 31 publications
5
212
1
7
Order By: Relevance
“…103 Conversely, Chang et al recently demonstrated the advantages of preconditioning MSCs in hypoxia, which was shown to improve the secretory capabilities of the cells (VEGF, HGF, and others), a main benefit of MSC therapy. 104 Gene therapy in MSCs has also received some attention, as Wang et al recently showed that adenoviral upregulation of protein kinase G1α improved MSC survival following implantation into a similar cardiac infarct model. 101 Additional recent studies have examined the possibility of exploiting endogenous signaling pathways in promoting MSC survival in a variety of wound healing contexts.…”
Section: Promotion Of Msc Survivalmentioning
confidence: 99%
“…103 Conversely, Chang et al recently demonstrated the advantages of preconditioning MSCs in hypoxia, which was shown to improve the secretory capabilities of the cells (VEGF, HGF, and others), a main benefit of MSC therapy. 104 Gene therapy in MSCs has also received some attention, as Wang et al recently showed that adenoviral upregulation of protein kinase G1α improved MSC survival following implantation into a similar cardiac infarct model. 101 Additional recent studies have examined the possibility of exploiting endogenous signaling pathways in promoting MSC survival in a variety of wound healing contexts.…”
Section: Promotion Of Msc Survivalmentioning
confidence: 99%
“…Sci China Life Sci, 2014Sci, , 57: 171 -180, doi: 10.1007 Although severe hypoxia can lead to cell death for certain cell types such as endothelial cells, repeated episodes of short periods' exposure to hypoxia (hypoxic-preconditioning) have shown conferring cytoprotective benefits. Research done in our laboratory and others has revealed that hypoxic-preconditioning protects bone marrow-derived mesenchymal stem cells (MSCs) from apoptosis and enhances cell survival after implantation [1,2]. However, the mechanisms underlying the beneficial effects of hypoxia preconditioned MSCs remain unclear.…”
Section: Citationmentioning
confidence: 99%
“…Research done in our laboratory and others has revealed that hypoxic-preconditioning protects bone marrow-derived mesenchymal stem cells (MSCs) from apoptosis and enhances cell survival after implantation [1,2]. However, the mechanisms underlying the beneficial effects of hypoxia preconditioned MSCs remain unclear.…”
mentioning
confidence: 99%
“…In addition, VEGF has neurotrophic and neuroprotective effects in vitro and in vivo [23,24]. Although several studies have demonstrated that VEGF mRNA or protein expression is upregulated in hypoxia-preconditioned MSCs [25][26][27], few reports have demonstrated the neuroprotective effects of hypoxia-preconditioned MSCs transplantation to treat SCI. Therefore, the present study aimed to determine whether hypoxia-preconditioned MSCs have a neuroprotective effect in vitro and in vivo and improve functional defects in a rat model of SCI.…”
Section: Introductionmentioning
confidence: 99%